2017
DOI: 10.1098/rspb.2017.1323
|View full text |Cite
|
Sign up to set email alerts
|

A possible structural correlate of learning performance on a colour discrimination task in the brain of the bumblebee

Abstract: Synaptic plasticity is considered to be a basis for learning and memory. However, the relationship between synaptic arrangements and individual differences in learning and memory is poorly understood. Here, we explored how the density of microglomeruli (synaptic complexes) within specific regions of the bumblebee (Bombus terrestris) brain relates to both visual learning and inter-individual differences in learning and memory performance on a visual discrimination task. Using whole-brain immunolabelling, we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 52 publications
6
50
3
Order By: Relevance
“…Developmental Neurobiology of modality-specific calyx subcompartments nor the resulting absolute numbers of PN boutons were quantified. We further noticed a significant discrepancy to our data regarding the absolute values for calyx volumes and PN bouton densities (a ~ 6× lower mean calyx volume and a ~ 2× lower number of PN boutons/1000 µm 3 in Li et al (2017) than in workers of the same age in our study), indicating that the authors largely underestimated bouton numbers, potentially due to errors introduced by obtaining complete volume scans and automated analyses of bouton densities (for a detailed discussion of this issue see Rössler et al, 2017). Clearly, to identify possible relationships between learning, long-term memory formation and MB plasticity in the bumble bee, further manipulation studies are needed.…”
Section: Figurecontrasting
confidence: 97%
See 1 more Smart Citation
“…Developmental Neurobiology of modality-specific calyx subcompartments nor the resulting absolute numbers of PN boutons were quantified. We further noticed a significant discrepancy to our data regarding the absolute values for calyx volumes and PN bouton densities (a ~ 6× lower mean calyx volume and a ~ 2× lower number of PN boutons/1000 µm 3 in Li et al (2017) than in workers of the same age in our study), indicating that the authors largely underestimated bouton numbers, potentially due to errors introduced by obtaining complete volume scans and automated analyses of bouton densities (for a detailed discussion of this issue see Rössler et al, 2017). Clearly, to identify possible relationships between learning, long-term memory formation and MB plasticity in the bumble bee, further manipulation studies are needed.…”
Section: Figurecontrasting
confidence: 97%
“…With this age‐related baseline now established, it will be crucial for the next step to investigate how the structural organization of the MB calyces can be further shaped throughout the adult life by means of sensory experience and long‐term memory formation as previously shown for other social insects (Hourcade et al , ; Riveros and Gronenberg, ; Falibene et al , ; Cabirol et al , ). A study by Li et al () focused on learning‐related volumetric and synaptic plasticity in the MB calyx of B. terrestris workers. They showed that PN bouton density in the collar correlated with learning and memory performance of different individuals in a visual discrimination task and, furthermore, increased with an increasing number of learned colors.…”
Section: Discussionmentioning
confidence: 99%
“…In fruit flies, visual reversal learning has also been shown to be improved by GABAergic inhibition [ 54 ], suggesting that sparse coding might be beneficial to solve this task. In honey bees, the density of synaptic boutons in the collar was not related to performance in a 2-colour discrimination task [ 55 ], but bumblebees with a high density of synaptic boutons in the collar have been shown to learn faster to discriminate between 10 different colours [ 56 ]. A possibility might be that increasing number of synaptic boutons in honey bees with greater experience might facilitate some learning tasks (not tested here) to the expense of others (such as reversal learning).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in chapter 4, behavioural observations of whether animals can succeed in tasks are not sufficient, but must be supplemented with an understanding of how they do so. While much research now focusses bottom-up approaches to improve our understanding of cognitive mechanisms (Cope et al 2018;Devaud et al 2015;Li et al 2017;Peng and Chittka 2017;Roper et al 2017;Vasas and Chittka 2019), the availability of accurate and more widely applicable tracking software provides a powerful tool for the advancement of the study of the intersection between individual and collective cognition (Graving et al 2019). More detailed long-term 7.1 Conclusion Chapter 7…”
Section: Resultsmentioning
confidence: 99%